A class of RUM choice models that includes the model in which the utility has logistic distributed errors. (September 2016) - del Castillo, J.M.
Highlights: A class of RUM models is defined. Several RUM models belonging to this class are introduced. Closed form expressions of the choice probabilities for these models are obtained. These RUM models are practical alternatives to the logit model. An application of these models to a sample is shown. Abstract: A class of random utility maximization (RUM) models is introduced. For these RUM models the utility errors are the sum of two independent random variables, where one of them follows a Gumbel distribution. For this class of RUM models an integral representation of the choice probability generating function has been derived which is substantially different from the usual integral representation arising from the RUM theory. Four types of models belonging to the class are presented. Thanks to the new integral representation, a closed-form expression for the choice probability generating function for these four models may be easily obtained. The resulting choice probabilities are fairly manageable and this fact makes the proposed models an interesting alternative to the logit model. The proposed models have been applied to two samples of interurban trips in Japan and some of them yield a better fit than the logit model. Finally, the concavity of the log-likelihood of the proposed models with respect to the utility coefficients is also analyzed.